The Reform of the Procedural Religious Court Law Based on Islamic Law in Indonesian Legal System - Abdullah Gofar (Sriwijaya Law Review, 2017)
The history of the development of religious courts and the inner atmosphere struggle of Muslims in Indonesia which faced the state’s political force in the New Order era has brought forth the religious procedural law. Article 54 of The 1989 Law No.7 stated that "the applicable law in the Religious Courts are applicable procedural law in the General Court, except those specifically regulated in this law." Philosophically, the Western law both civil substantive law (Burgerlijke Wetboek) and formal law/civil procedure (HIR and Rbg), prepared using the approach of individualism, secular, the optical properties of the nature legal dispute was seen as objects (Zaak) which is sheer material. While the substantive law in religious courts is the law derived from Islamic law that stem from philosophical values of Islam. So, the presence of the Religious Courts in the scope of judicial in Indonesia still raises problems, including: Why is the western law of civil procedure which promote the value of materialism and formal correctness adopted into religious procedural law, whereas the philosophical orientation is not aligned with the substantive law based on Islamic law, and what are the efforts to reform the reformulation of procedural law of religious courts.